(untitled) (Eurasian Journal of Engineering and Technology, 2026)
The article presents the contemporary trends in the development of cinema art and provides their socio-philosophical analysis. It examines the digitization of the film production process, the increased accessibility of modern technologies, and offers reflections on the outcomes of these changes.